Repurposing of MitoTam: Novel Anti-Cancer Drug Candidate Exhibits Potent Activity against Major Protozoan and Fungal Pathogens - Arbon, Dominik; Ženíšková, Kateřina; Šubrtová, Karolína; Mach, Jan; Štursa, Jan; Machado, Marta; Zahedifard, Farnaz; Leštinová, Tereza; Hierro-Yap, Carolina; Neuzil, Jiri; Volf, Petr; Ganter, Markus; et al. (Antimicrobial agents and chemotherapy, 2022)
Many of the currently available anti-parasitic and anti-fungal frontline drugs have severe limitations, including adverse side effects, complex administration, and increasing occurrence of resistance. The discovery and development of new therapeutic agents is a costly and lengthy process. Therefore, repurposing drugs with already established clinical application offers an attractive, fast-track approach for novel treatment options. In this study, we show that the anti-cancer drug candidate MitoTam, a mitochondria-targeted analog of tamoxifen, efficiently eliminates a wide range of evolutionarily distinct pathogens in vitro, including pathogenic fungi, Plasmodium falciparum, and several species of trypanosomatid parasites, causative agents of debilitating neglected tropical diseases. MitoTam treatment was also effective in vivo and significantly reduced parasitemia of two medically important parasites, Leishmania mexicana and Trypanosoma brucei, in their respective animal infection models. Functional analysis in the bloodstream form of T. brucei showed that MitoTam rapidly altered mitochondrial functions, particularly affecting cellular respiration, lowering ATP levels, and dissipating mitochondrial membrane potential. Our data suggest that the mode of action of MitoTam involves disruption of the inner mitochondrial membrane, leading to rapid organelle depolarization and cell death. Altogether, MitoTam is an excellent candidate drug against several important pathogens, for which there are no efficient therapies and for which drug development is not a priority.
Keywords: protinádorové látky; Drug Repositioning; Antineoplastic Agents; Animals; Plasmodium falciparum; Membrane Potential, Mitochondrial; membránový potenciál mitochondrií; přehodnocení terapeutických indikací léčivého přípravku; zvířata; Trypanosoma brucei brucei